Comparison of efficacy of nebulized ketamine with morphine and intravenous morphine in pain reduction in patients with traumatic long-bone fractures admitted to emergency department - Reza Azizkhani; Kourosh Akhbari; Babak Masoumi; Abdolrahman Parna; Keihan Golshani (Archives of Trauma Research, 2018)
Background: Traumatic long-bone fracture is a common cause of referring to the emergency department (ED). The aim of this study was to compare the efficacy of nebulized ketamine and morphine and intravenous (IV) morphine in reducing pain in these patients. Materials and Methods: In this clinical trial study, 88 patients with traumatic long-bone fractures referred to the ED were randomly selected and divided into two groups of nebulized ketamine and morphine and IV morphine using block randomization. Changes in pain intensity according to visual analog scale (VAS), patient satisfaction, and clinical features, including oxygen saturation (O2 sat), systolic blood pressure (SBP), respiratory rate, and pulse rate (PR) were assessed at baseline and 15 and 30 min after the intervention and finally, data were analyzed using the SPSS software. Results: Demographic characteristics including sex, age, and site of fracture were similar in the two groups (P > 0.05). In the IV morphine group, O2 sat (P < 0.001), SBP (P = 0.005), and PR (P < 0.001) significantly decreased, but in the nebulized group, SBP (P < 0.001) and PR (P < 0.001) significantly increased, but O2 sat did not significantly decrease (P > 0.05). The VAS results in the IV group were better at 15 min (P < 0.001), but after 30 min, both methods were equally effective in pain reduction (P = 0.508). Conclusion: According to the results of this study, the pain reduction was similar in both groups after 30 min, but regarding other parameters such as patients' satisfaction and fewer side effects, it can be concluded that the long-term effect of nebulized morphine and ketamine would be more beneficial.